How to measure peripherality at the city scale. A model proposal - Grosel, Mikołaj (Bulletin of Geography. Socio-economic Series, 2024)
The phenomenon of peripherality is increasingly applied to urban space. At the same time, there is no scientific consensus on how to analyse and measure peripherality. This article presents a tool for analysing peripherality at the urban scale – the Opportunity Potential Model (OPM) – based on the intervening opportunity mechanism. The article describes how the model works and presents an example of its use: an analysis of the peripherality of the Jagodno neighbourhood in Wrocław (Poland). The model takes into account three dimensions of peripherality (geographical, material and social) to create a comprehensive analysis. The case study shows not only the degree of peripherality of the study area but, above all, the possibilities of the model – its advantages and disadvantages in the process of peripherality analysis and possible further uses.